"Nature of the firm: origins, evolution and development/ edited by Oliver E. Williamson and Sidney G. Winter" - "Williamson, Oliver E. (ed.);Winter, Sidney G. (ed.)" (Oxford, 1993)
In 1937, Ronald H. Coase published "The Nature of the Firm," a classic paper that raised fundamental questions about the concept of the firm in economic theory. Coase proposed that the comparative costs of organizing transactions through markets rather than within firms are the primary determinants of the size and scope of firms. Coase won the 1991 Nobel Prize in Economics for this work. This volume derives from a conference held in 1987 to commemorate the fiftieth anniversary of the publication of Coase's classic article. The first chapter affords an overview of the volume. It is followed by a republication of the 1937 article, and by the three lectures Coase presented at the conference. These lectures provide a lively and informative history of the origins and development of his thought. Subsequent chapters explore a wide-range of theoretical and empirical issues that have arisen in the transaction cost economic tradition. They illustrate the power of the transaction cost approach to enhance understanding not only of business firms, but of problems of economic organization generally. In addition to Coase's work, contributors include Sherwin Rosen, Paul Joskow, Oliver Hart, Harold Demsetz, Scott Masten, Benjamin Klein, as well as the volume's editors, Oliver E. Williamson, and Sidney G. Winter. The Nature of the Firm includes Coase's acceptance speech for his Nobel Prize in Economics.
Keywords: Industrial organization